In-situ analysis on formation of micropores by Rayleigh instability in solidification of Sn-Ni alloy. (December 2020) - Peng, Peng; Yue, Jinmian; Zhang, Anqiao; Zhang, Xudong; Xu, Yuanli
Abstract: A new formation mechanism of micropores whose radii are approximately 1 μm is investigated during solidification of Sn-Ni alloy through the in-situ observation by confocal laser scanning microscope. A series of liquid lines which are closely related to the stability of the growing L/Ni3 Sn2 interface were formed during solidification, then, these liquid lines decomposed into different rows of liquid droplets by Rayleigh instability in solid Ni3 Sn2 phase. The relationship between the formation of the micropores and the liquid droplets is confirmed. In addition, the distribution of the radii of the micropores agrees with the prediction of the Rayleigh instability theory. Graphical abstract: Image, graphical abstract